Effect of Family Role and Law Enforcement Agencies Impact Analysis of Meth Mathematical Model of Drug Crime of Users in Nigeria - O, Akpienbi Isaac; T, Ezra E. (Darul Yasin Al Sys, 2024)
This paper introduces a mathematical model that incorporates family dynamics and law enforcement into the transmission of methamphetamine and drug-related crime. The model's dynamic behavior, equilibrium existence, and global stability are analyzed using mathematical techniques. The research includes the exploration of equilibrium states representing drug crime-free and drug crime-persistent scenarios, as well as the determination of the reproduction number. The findings demonstrate that the drug crime-free equilibrium and drug crime-persistent equilibrium are asymptotically stable. Moreover, the study advises the government to develop and implement policies and strategies aimed at controlling and eradicating drug crime in Nigeria, with a specific focus on law enforcement agencies undertaking the implementation process.